2020
DOI: 10.1111/dom.14161
|View full text |Cite
|
Sign up to set email alerts
|

Effects of insulin degludec and insulin glargine U300 on glycaemic stability in individuals with type 1 diabetes: A multicentre, randomized controlled crossover study

Abstract: To compare the effects of insulin degludec (IDeg) and insulin glargine U300 (IGlarU300) on glycaemic stability in subjects with type 1 diabetes. Materials and methods: In this multicentre, crossover trial, 46 individuals with type 1 diabetes and essentially undetectable circulating C-peptide were randomly assigned to either the IDeg-first/IGlarU300-second group or the IGlarU300-first/IDeg-second group, and were treated with the respective basal insulins for 4-week periods. Data were collected in the last week … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(66 citation statements)
references
References 35 publications
0
66
0
Order By: Relevance
“…Limited evidence is available in the T1D population using CGM and about the comparison between first-and second-generation basal insulins and between the two second-generation basal insulins. A current study conducted by Miura et al comparing the effects of IDeg and Gla-300 on glycemic stability in T1D patients using CGM concluded that both insulins were comparable in terms of glucose-stabilizing effects [23]. These results were also observed in terms of glycemic control in the type 2 diabetes (T2D) population when comparing Glar-300 and IDeg using a CGM device [24].…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Limited evidence is available in the T1D population using CGM and about the comparison between first-and second-generation basal insulins and between the two second-generation basal insulins. A current study conducted by Miura et al comparing the effects of IDeg and Gla-300 on glycemic stability in T1D patients using CGM concluded that both insulins were comparable in terms of glucose-stabilizing effects [23]. These results were also observed in terms of glycemic control in the type 2 diabetes (T2D) population when comparing Glar-300 and IDeg using a CGM device [24].…”
Section: Introductionmentioning
confidence: 73%
“…The results regarding pharmacodynamics vary. Recently, Miura et al reported the effects of both insulins on glycemic stability in c-peptide-negative T1D patients using CGM [23]. In a multicenter randomized crossover design including 46 patients, the authors suggested that Glarg-300 and IDeg-100 have comparable stabilizing effects on the glucose profile.…”
Section: Discussionmentioning
confidence: 99%
“…However, another double-blind crossover euglycemic clump study showed that Deg exhibited lower day-to-day and withinday GV than that of Gla-300 in type 1 diabetes [28]. Recently, Miura et al conducted multicenter crossover trial on type 1 diabetes in which the e ciency of Deg and Gla-300 were compared [29]. In this study, SD-FBG by CGM were evaluated as the marker of day-to-day GV.…”
Section: Discussionmentioning
confidence: 96%
“…In clinical studies with patients with T1D, degludec has shown reduced risk for hypoglycemia while inducing similar glycemic control as compared to glargine U100 (Heller et al, 2012). When compared to glargine U300, degludec has shown a similar glucose-lowering effect in this patient population (Miura et al, 2020). Given its prolonged effect, degludec allows increased flexibility in the timing of administration, but it may impose a challenge in the inpatient setting where there is a need for faster dose titration.…”
Section: Basal Insulinsmentioning
confidence: 99%